HUBUNGAN AKTIVITAS FISIK DENGAN KENAIKAN BERAT BADAN PADA MAHASISWA FK UMSU ANGKATAN 2018 DI MASA PANDEMI - RAFLESEPTIAWAN IRSYAD AUFA; ROBITAH ASFUR (JURNAL ILMIAH SIMANTEK, 2023)
Physical activity is the expenditure of energy produced by muscles. Weight gain is an increase in body mass. This study aims to determine the relationship between physical activity and weight gain in FK UMSU students class of 2018. This research is an analytic study with a cross sectional design. The research sample amounted to 99 FK UMSU students class of 2018 who were taken by simple random sampling method. This study was tested with the Kolmogorov-Smirnov test. Overall, the results showed that the dominant picture of student physical activity was low physical activity (83%). Then the dominant body weight picture is a fixed body weight (57%). There is no relationship between physical activity and weight gain in FK UMSU students class of 2018 during the pandemic.